Kualitas Audit: Mengidentifikasi Faktor-Faktor Pendorong dan Penghambat - Oktarina, Dian; Ramadiani, Nabila Aurelia (Jurnal Akuntansi AKUNESA, 2024)
This research was conducted to determine the factors that encourage and inhibit the implementation of quality audits. These factors include independence, objectivity, time budget pressure, and work experience. Data was collected through questionnaires distributed to auditors at the Public Accounting Firm in Surabaya. This research uses a purposive sampling method with research sample criteria using auditors who work at the Public Accounting Firm in Surabaya, which is registered in the IAPI 2023 directory. The sample used was 97 auditors. The data in this study was processed using PLS-SEM. The result of this research state that independence, objectivity, and work experience influence audit quality. Then, time budget pressure does not affect audit quality.